Efficacy of task-oriented training on balance ability in people with multiple sclerosis: A systematic review and meta-analysis. - Alashram, Anas R. (Journal of Bodywork & Movement Therapies, 2025)
To examine the influences of Task-oriented (TO) training on balance ability in people with multiple sclerosis (PwMS). A comprehensive search was conducted in the following databases: "PubMed, Web of Science, Scopus, EMBASE, REHABDATA, and PEDro" until August 2023. Experimental trials that included PwMS administered TO training, compared with controls or with no controls, and assessed balance were included. The "Physiotherapy Evidence Database (PEDro) scale" was used to determine the methodological quality. A total of nine studies met the selection criteria. In total, 231 PwMS (42.03 years), 59.87 % of whom were women, were included in the current review. The "PEDro scale" scores ranged from tew to eight, with a median score of six. The meta-analysis of five studies assessing the effect of interventions on the Berg Balance Scale (BBS) showed a small to moderate mean effect size (d = 0.462), but this was not statistically significant (95 % CI: 0.334 to 1.258; p = 0.255). High heterogeneity (I2 = 82 %) and a wide prediction interval (−2.445 to 3.369) indicate considerable variability in true effects across studies. These findings suggest inconsistent outcomes and highlight the need for cautious interpretation and further research. The preliminary findings revealed that the evidence for the effects of combining TO training and conventional physiotherapy on balance in PwMS is promising. Further studies are warranted to specify the optimal treatment protocol and to recognize the influences of TO training on balance in PwMS.